Effective an instructional in program in the development of some of the moral values on the children of kindergarten (Journal Of Educational and Psychological Researches, 2010)
The research aims to 1 – The discloser  of the level of moral values in the children of kindergarten. 2 - Building an educational program designed to develop moral values on the children of kindergarten. 3 - Knowing the impact of the program in the development of moral values in children Purposive sample was selected consisted of 40 children and a child aged 5-6 years and to achieve objectives of the research promising measure of the moral  values kindergarten has been applied to the children of the two groups was based on  pre and post test Results of search - No statistically significant difference level of significance of 5% between the average scores of the experimental group and the average scores of the control group in pretest - There is a statistically significant difference between the scores of the experimental group at pretest and post test and the level of significance of 5% for post test .